Experiência da Secretaria de Saúde de Goiânia - Marques, Camila Marçal; Baía, Lorena; Barbosa, Maria Tania de Oliveira; de Sousa, Wellinton Aurélio (Experiências Exitosas de Farmacêuticos no SUS, 2015)
Experiência da Secretaria de Saúde de Goiânia